Crecimiento, mortandad y estado fitosanitario de la especie Dipteryx charapilla de la plantación N° 36 del CIEFOR - Puerto Almendra, Loreto - Perú. 2021 - Vizcarra Vargas, David (2023)
The study was carried out in Forest Parcel No. 36 of 1 ha in CIEFOR - Puerto Almendras, evaluating 200 Dipteryx charapilla plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by band 8 with a value of 0,06 mm between the first and last evaluation. Likewise, in height the greatest increase was presented by band 7 with a value of 5,61 cm. The Chi-square test indicates that there is a significant difference between the averages of increase in diameter - height and the bands (p-value = 0,00 <? = 0,05). The survival of cedar plants varies between 75% to 100% survival, while mortality varies between 10% to 25%. The highest number of plants presented GOOD quality with 129 seedlings that represents 71,27% of the total, followed by REGULAR quality with 35 live individuals that indicates 19,34% and, finally, the least amount of individuals were observed in BAD quality with 17 seedlings that represented 9,39 % of the total. At a general level in the experiment Good quality was recorded for the Dipteryx charapilla seedlings at the end of the study. Similar studies are needed with other native forest species in CIEFOR - Puerto Almendras.